Evaluation of Velocity through the Factory of Strepsils Brand in Reckitt Benckiser Nottingham Plant - Batili, Burcin (2009)
Today many companies face problems with WIP inventory management. The importance of effective WIP control and inventory management has become more evident in order to reduce manufacturing lead time. Managing WIP inventory is the focus of this dissertation. It combines theory obtained from literature, the manufacturing system analysis done throughout the ten weeks internship period in the company and the simulation results to explore the opportunities associated with how Reckitt Benckiser can improve the WIP control and management of Strepsils lozenges. This dissertation recognizes that WIP control and management is highly in interaction with batch sizes, space utilization and material flow independent from the production control system particularly for the Strepsils manufacturing environment. Furthermore, it explores the problems and some of the seven wastes defined by Taichi Ohno which are occurred due to poor control of these aspects. Hence, it emphasizes effective material handling in terms of storage, as well as the necessity of small batch production. It presents new material handling design and the operating procedure for logistical operations in the WIP inventory storage area to utilize space more effectively against the fullness risk of storage areas and to improve material flow. It indicates the necessity of simultaneous quality control at least for the bulks produced more and frequently to give more storage flexibility and to reduce manufacturing lead time. Also, it indicates the putting of colourful tags with bag numbers onto bulk bags to facilitate the visual identification. Besides, it recognizes the inadequacy of manufacturing performance and emphasizes the requirement of increased OEE figures to meet the demand based on the simulation results. Hereby, it proves that changeover time reduction of bulk production equipments is prerequisite both for improvement in manufacturing performance and for facilitating small batch production. Consequently, the explored opportunities will provide a more appropriate WIP control and inventory management to the company for Strepsils lozenges and also will directly improve the velocity through the factory of Strepsils.